2020
DOI: 10.21203/rs.3.rs-112924/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Role of Eco-Friendly Soil Amendments Co-Application on the Performance of Lingrain (Linum Usitatissimum L.) Under Late-Season Irrigation Limitation

Abstract: This study's main purpose was to investigate the probable amelioration of limited irrigation conditions by soil amendments for lingrain plants. The experiment was accomplished as a completely randomized factorial design along with three replications. The first factor was green manure (without (Gc) and with Trifolium pratense (Gr)), the second factor consisted of Rhizophagus irregularis mycorrhiza (Fm), vermicompost (Fv), both of mycorrhiza and vermicompost (Fm+v) and none of them (Fc), and also the third facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 71 publications
0
5
0
Order By: Relevance
“…Their research demonstrated a variety of significant advancements in plant variables. A notable observation was the elevation of leaf moisture content [16]. This indicates that a synergistic treatment augmented the plant's capacity for water retention, which is vital for its overall well-being.…”
Section: Effect Of Organic Matter On Amf Colonizationmentioning
confidence: 94%
See 4 more Smart Citations
“…Their research demonstrated a variety of significant advancements in plant variables. A notable observation was the elevation of leaf moisture content [16]. This indicates that a synergistic treatment augmented the plant's capacity for water retention, which is vital for its overall well-being.…”
Section: Effect Of Organic Matter On Amf Colonizationmentioning
confidence: 94%
“…This indicates that the mutually beneficial association between mycorrhiza and roots was fortified, resulting in improved nutrient assimilation. Apart from root colonization, Lingrain plants treated with the consortium demonstrated elevated nitrogen levels [16]. Nitrogen is a crucial nutrient for plant growth and development, implying that the combined treatment promoted enhanced nutrient availability for the plants.…”
Section: Effect Of Organic Matter On Amf Colonizationmentioning
confidence: 99%
See 3 more Smart Citations